European Expert Opinion on Infrarenal Sealing Zone Definition and Management in Endovascular Aortic Repair Patients: A Delphi Consensus. (June 2023) - de Vries, Jean-Paul P. M.; Zuidema, Roy; Bicknell, Colin D.; Fisher, Robert; Gargiulo, Mauro; Louis, Nicolas; Oikonomou, Kyriakos; Pratesi, Giovanni; Reijnen, Michel M. P. J.; Valdivia, Andrés Reyes; Riambau, Vincent; Saucy, François
Purpose: The purpose of the study was to provide a consensus definition of the infrarenal sealing zone and develop an algorithm to determine when and if adjunctive procedure(s) or reintervention should be considered in managing patients undergoing endovascular aortic repair (EVAR) for infrarenal abdominal aortic aneurysm (AAA). Methods: A European Advisory Board (AB), made up of 11 vascular surgeons with expertise in EVAR for AAA, was assembled to share their opinion regarding the definition of preoperative and postoperative infrarenal sealing zone. Information on their current clinical practice and level of agreement on proposed reintervention paths was used to develop an algorithm. The process included 2 virtual meetings and 2 rounds of online surveys completed by the AB (Delphi method). Consensus was defined as reached when ≥ 8 of 11 (73%) respondents agreed or were neutral. Results: The AB reached complete consensus on definitions and measurement of the pre-EVAR target anticipated sealing zone (TASZ) and the post-EVAR real achieved sealing zone (RASZ), namely, the shortest length between the proximal and distal reference points as defined by the AB, in case of patients with challenging anatomies. Also, agreement was achieved on a list of 4 anatomic parameters and 3 prosthesis-/procedure-related parameters, considered to have the most significant impact on preoperative and postoperative sealing zones. Furthermore, the agreement was reached that in the presence of visible neck-related complications, both adjunctive procedure(s) and reintervention should be contemplated (100% consensus). In addition, adjunctive procedure(s) or reintervention can be considered in the following cases (% consensus): insufficient sealing zone on completion imaging (91%) or on the first postoperative computed tomography (CT) scan (91%), suboptimal sealing zone on completion imaging (73%) or postoperative CT scan (82%), and negative evolution of the actual sealing zone over time (91%), even in the absence of visible complications. Conclusions: AB members agreed on definitions of the pre- and post-EVAR infrarenal sealing zone, as well as factors of influence. Furthermore, a clinical decision algorithm was proposed to determine the timing and necessity of adjunctive procedure(s) and reinterventions.